2010
DOI: 10.1038/ni.1902
|View full text |Cite
|
Sign up to set email alerts
|

Roquin binds inducible costimulator mRNA and effectors of mRNA decay to induce microRNA-independent post-transcriptional repression

Abstract: The molecular mechanism by which roquin controls the expression of inducible costimulator (ICOS) to prevent autoimmunity remains unsolved. Here we show that in helper T cells, roquin localized to processing (P) bodies and downregulated ICOS expression. The repression was dependent on the RNA helicase Rck, and roquin interacted with Rck and the enhancer of decapping Edc4, which act together in mRNA decapping. Sequences in roquin that confer P-body localization were essential for roquin-mediated ICOS repression.… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

10
222
0

Year Published

2011
2011
2021
2021

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 163 publications
(234 citation statements)
references
References 36 publications
(38 reference statements)
10
222
0
Order By: Relevance
“…As indicated by our analytical ultracentrifugation experiments, monomeric ROQUIN1 predominates at lower protein concentrations, but a concentration-dependent dimerization of Roquin has been reported by Schlundt et al 20 Since Roquin proteins accumulate in P bodies and stress granules 3,21 , it is tempting to speculate that elevated Roquin concentration at these sites might favour the formation of functional dimers.…”
Section: Discussionmentioning
confidence: 86%
See 1 more Smart Citation
“…As indicated by our analytical ultracentrifugation experiments, monomeric ROQUIN1 predominates at lower protein concentrations, but a concentration-dependent dimerization of Roquin has been reported by Schlundt et al 20 Since Roquin proteins accumulate in P bodies and stress granules 3,21 , it is tempting to speculate that elevated Roquin concentration at these sites might favour the formation of functional dimers.…”
Section: Discussionmentioning
confidence: 86%
“…1). The expression of ICOS (inducible T-cell costimulator), a gene encoding an essential receptor for follicular T-cells, is also restricted by Roquin, which promotes the degradation of ICOS mRNA, thereby playing an important role in autoimmunity 2,3 .…”
mentioning
confidence: 99%
“…The alternative splicing of CD45RA to CD45RO is one of the hallmarks of memory T-cell differentiation (28). The stability of ICOS mRNA, which is governed by the RBPs Roquin-1 and -2, restrains the differentiation of follicular helper T cells (29)(30)(31)(32)(33). The RBPs Zfp36l1 and Zfp36l2 suppress Notch1 mRNA stability, regulating normal thymocyte differentiation and preventing malignant transformation (34).…”
Section: Discussionmentioning
confidence: 99%
“…However, some studies showed that roquin represses autoimmunity by limiting ICOS mRNA expression through a microRNA-independent posttranslational repression. 33,34 In addition, a recent study showed that the loss of roquin induced early death and immune dysregulation but not autoimmunity in sanroque mice. 35 Therefore, future studies are required to completely elucidate the mechanisms behind pathogenesis of lupus in sanroque mice.…”
Section: T Fh Cells In Murine Models Of Autoimmune Diseasesmentioning
confidence: 99%